Determination of aragonite trace element distribution coefficients from speleothem calcite–aragonite transitions. (1st October 2016) - Wassenburg, J.A.; Scholz, D.; Jochum, K.P.; Cheng, H.; Oster, J.; Immenhauser, A.; Richter, D.K.; Häger, T.; Jamieson, R.A.; Baldini, J.U.L.; Hoffmann, D.; Breitenbach, S.F.M.
Abstract: The processes that govern the incorporation of (trace) elements into speleothems can often be linked to environmental changes. Although element incorporation into speleothem calcite is now reasonably well understood, current knowledge regarding trace element variability in speleothem aragonite is very limited. Of particular interest is whether trace element distribution coefficients are above or below one in order to assess the extent to which prior aragonite precipitation has affected speleothem aragonite trace element records. This study uses nine calcite-to-aragonite transitions in seven speleothems from diverse environmental settings to derive the first quantitative estimates of the distribution coefficients for several elements in speleothem aragonite: D Mg(Ar) = 9.7E−5 ± 9.01E−5, D Ba(Ar) = 0.91 ± 0.88, D Sr(Ar) = 1.38 ± 0.53, and D U(Ar) = 6.26 ± 4.54 (1 σ SD). For one speleothem from western Germany, the distribution coefficients are generally higher, which is potentially related to the very low growth rates (<11 μm/year) of this sample. In particular, D Sr(Ar) appears to show a negative correlation with growth rate when growth rate is below 20 μm/year. In summary, our results demonstrate that speleothem aragonite D Mg(Ar) is below one, D U(Ar) is considerably above one, and D Sr(Ar) is above one or close to unity. For D Ba(Ar), reaching a similar conclusion is difficult due to the relatively high uncertainty. Enhanced prior aragonite precipitation will thus result in lower U and higher Mg concentrations in speleothem aragonite, although in many cases Mg in speleothem aragonite is most likely dominated by other processes. This result suggests that U concentrations in aragonitic stalagmites could serve as a very effective proxy for palaeo-rainfall.